2010
DOI: 10.1007/s11605-009-1039-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study between Clipless Laparoscopic Cholecystectomy by Harmonic Scalpel Versus Conventional Method: A Prospective Randomized Study

Abstract: HS provides a complete hemobiliary stasis and is a safe alternative to stander clip of cystic duct and artery. It provides a shorter operative duration, less incidence of gallbladder perforation, less postoperative pain, and less rate of conversion to open cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
99
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(111 citation statements)
references
References 29 publications
10
99
2
Order By: Relevance
“…Besides the common use of clips, various other techniques of securing cystic duct and arteries have been introduced. Harmonic scalpel and "LigaSure" in LC has come up recently (Kandil et al, 2010;Huscher et al, 2009). Cost of equipment is the main prohibitory factor in developing country like Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the common use of clips, various other techniques of securing cystic duct and arteries have been introduced. Harmonic scalpel and "LigaSure" in LC has come up recently (Kandil et al, 2010;Huscher et al, 2009). Cost of equipment is the main prohibitory factor in developing country like Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] any event of inappropriate control of cystic artery was documented soon after the procedure and amount of blood loss was also measured and noted.…”
Section: Methodsmentioning
confidence: 99%
“…According to a retrospective case series by Gelmini et al, 12 the use of the Harmonic scalpel in LC is associated with a significantly shorter median operative time, as compared to that of conventional monopolar electrocautery coagulation: 60 min (range, 20-205 min) vs 85 min (45-150 min); P < .001. Zanghi et al 13 also reported in a retrospective study of 164 patients that the use of the Harmonic scalpel is associated with a significantly shorter mean operative time (35 ± 10 vs 56 ± 12 min, P < .001); and Kandil et al 14 reported in a prospective, randomized study that the use of the Harmonic scalpel alone for dissection and sealing in LC resulted in almost half the mean operative time (33.2 ± 9.6 vs. 51.7 ± 13.8 min, P = .001).The reduction in operative time with HS is due to decease smoke production during dissection as well as better homeostasis.…”
Section: Discussionmentioning
confidence: 97%
“…In previous studies reporting the use of the Harmonic scalpel with less postoperative pain, the major cause may be a significantly shorter operative time for LC with a Harmonic scalpel than with Monopolar electrocautery. 14 …”
Section: Discussionmentioning
confidence: 99%